Pleural interventions: management of acute and chronic pneumothorax. - Rahman, N; Davies, R; Gleeson, F (2008)
Pneumothorax is a common clinical entity that may present to a wide variety of medical specialties. Primary pneumothorax (in the presence of no known underlying lung disease) and secondary pneumothorax (in known lung disease) are distinct entities with varied etiology, treatment, and prognosis. Diagnosis is usually based on clinical history and basic radiology, but more advanced radiological techniques may be required in certain circumstances. There is relatively little evidence on which to base management decisions in patients with pneumothoraces, and many important aspects of management (e.g., aspiration vs intercostal drainage, chest drain size, use of suction) are often based on best practice and expert opinion. The etiology of pneumothorax will often inform the clinician whether a more conservative or more invasive approach is required. Radiological intervention techniques are valuable in the treatment of complicated pneumothoraces and in certain clinical situations.